Evaluation of factors associated with chronic non-communicable diseases and their relationship with the consumption of vitamins A, C and E in women under preventive gynecological follow-up (Research, Society and Development, 2020)
Chronic Non Communicable Diseases (NCD) are conditions that impact the quality of life of the population. The antioxidant vitamins - among them the vitamins A, C and E - are micronutrients that regulate the process of oxidative stress, present in the etiology of these diseases. Therefore, the objective of this quantitative and transversal study was to evaluate the factors associated with diabetes mellitus type 2, systemic arterial hypertension and obesity, especially those factors linked to the consumption of antioxidant vitamins in 112 women in preventive gynecological follow-up in an oncologic reference unit of the city of Francisco Beltrão, PR, Brazil.  For the data collection, two questionnaires were applied to evaluate the nutritional and health status of the participants, anthropometric data, socioeconomic information, presence of comorbidities and consumption of food sources of antioxidant vitamins through the Questionnaire of Food Frequency (QFA). The results showed that 8.9% of the population who was studied had DM2, having as factors associated with minimum age of 50 years, presence of HAS and consumption of vitamin A. In the case of SAH, there was a prevalence of 32.1% and the only factor effectively associated was the presence of DM2. For obesity, no significant factor associated with it was observed. This study reinforces the evidence that the adequate intake of fruits and vegetables, for being sources of antioxidant nutrients, should be stimulated to prevent NCD. However, it is necessary to expand the studies on their relationship with these pathologies in a more generalist way.